ANALYSIS OF THE STRUCTURE OF NIGERIA’S INDEPENDENT NATIONAL ELECTORAL COMMISSION (1999-2011) - Omeiza, Moveh David (European Scientific Journal, ESJ, 2012)
The structure of election administration is a crucial component of the democratic project of any state. In Nigeria, it is widely acknowledged that the structural character of the country’s election management body –the Independent National Electoral Commission (INEC) has over the years become the focal points at which elections are compromised. With insights from interviews and focused group discussion; conducted amongst INEC commissioners, staff and representatives of political parties within the period: 2009-2011, this paper is a graphic analysis of how the structure of INEC complicates the election administration process and democratic sustainability in Nigeria.